1985
DOI: 10.1017/s0022172400062409
|View full text |Cite
|
Sign up to set email alerts
|

Bluetongue virus and epizootic haemorrhagic disease of deer virus serotypes in northern Colombian cattle

Abstract: SUMMARYThere is recent evidence of bluetongue (BT) and epizootic haemorrhagic disease (EHD) virus infection of cattle in the American tropics, including BT group reactive antibody in Colombian cattle. These observations prompted a study to determine serologically the specific BT and EHD virus types present, and time of infection and to collect Culicoides spp. as potential vectors. A prospective study of BT and EHD virus infection was done on two farms in the Colombian department ofAntioquia. Sequential samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…Homan et al (1985aHoman et al ( ,b,c, 1990Homan et al ( , 1992) detected a seroprevalence of 48.1% in cattle in Costa Rica and a seroprevalence of 51.8% in Córdoba and Antioquia, two departments in the north of Colombia. These authors also detected and reported the presence of serotypes 1, 6, 12, 14 and 17 in Antioquia (Homan et al, 1985c) (Fig. 2 and Table 1).…”
Section: Btv In South Americamentioning
confidence: 55%
“…Homan et al (1985aHoman et al ( ,b,c, 1990Homan et al ( , 1992) detected a seroprevalence of 48.1% in cattle in Costa Rica and a seroprevalence of 51.8% in Córdoba and Antioquia, two departments in the north of Colombia. These authors also detected and reported the presence of serotypes 1, 6, 12, 14 and 17 in Antioquia (Homan et al, 1985c) (Fig. 2 and Table 1).…”
Section: Btv In South Americamentioning
confidence: 55%
“…Se han presentado epidemias en varios países como Grecia, Turquía, Israel, España y Portugal (1). En Colombia, la abundancia de C. insignis se ha asociado con la transmisión del virus de la lengua azul encontrado en ganado bovino en el departamento de Antioquia (11).…”
Section: La Enfermedad Más Importante Transmitida Porunclassified
“…It is assumed, therefore, that the epidemiological features of EHDV infection mirror those of BTV. Thus, although less well documented on a global basis, the distribution of EHDV infection likely is similar to that of BTV and includes tropical and temperate regions throughout the world between latitudes of approximately 40-50°N and 35°S (4,25,31,37,38,44,45,46,47,48,49,50,51,52). It is assumed, but not well proven, that the specific vector species differ throughout the world.…”
Section: Epidemiology and Modes Of Transmissionmentioning
confidence: 99%
“…Since the initial description of EHD in the eastern United States, EHDV infection of wild and domestic ungulates has been identified elsewhere in the Americas (including the Caribbean islands and both Central and South America), Africa, Asia (including Eastern, Central and Southeast Asia), Australia, Indian Ocean islands such as Mauritius and Reunion, and the Middle East (4,14,16,25,30,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Although infection of domestic livestock is prevalent in many endemic areas, EHDV only rarely causes overt disease in livestock species and apparently only in cattle and not small ruminants (4,23).…”
Section: Introductionmentioning
confidence: 99%